Agarose Gel Electrophoresis Reveals the Molecular Weight Distribution of Hyaluronan Produced by Orbital Fibroblasts - Erika Galgoczi; Monika Katko; Sara Borbely; Istvan Orsos; Zsanett Molnar; Bernadett Ujhelyi; Zita Steiber; Endre V. Nagy (Gels, 2025)
Thyroid eye disease (TED) is characterized by autoimmune inflammation and structural remodelling of orbital tissues, which is a consequence of the activation of orbital fibroblasts (OFs). As a result of this activation, the production of hyaluronan (HA) and the proliferation and adipocyte differentiation of OFs are enhanced. Adipogenesis leads to additional accumulation of HA. The aim of this study was to elucidate the molecular weight distribution of HA produced by OFs under basic conditions and after adipogenic stimuli. The concentration and the molecular weight distribution of HA were examined using ELISA and agarose gel electrophoresis, respectively, in TED (n = 3) and non-TED (n = 3) OF cultures. Under adipogenic stimuli, HA production is increased in OFs. In TED OF cultures, which, unlike non-TED OFs, can differentiate into adipocytes, the enhanced proportion of high-molecular-weight (HMW) HA of more than 2000 kDa is responsible for the increased HA concentration in the culture media. In non-TED OF cultures, which contain a negligible number of differentiating cells after adipogenic stimulation, the medium-molecular-weight (MMW) HA fragments from 50 to 1000 kDa also contribute to the enhanced HA content. Increased production of HMW-HA during adipocyte differentiation of TED OFs is responsible for the elevated HA content in the culture media, which may be an important contributor to both connective tissue matrix expansion and edema in the pathogenesis of TED.